Production of cyclodextrin glucanotransferase from alkalophilic Bacillus sp. TS1-1: Optimization of carbon and nitrogen concentration in the feed medium using central composite design - Wan Md. Zain, Wan Salwanis; Illias, Rosli; Md Salleh, Madihah; Hassan, Osman; Abdul Rahman, Roshanida; Abdul Hamid, Aidil (Elsevier Inc., 2007)
Optimisation of nutrient feeding was developed to overcome the limitation in batch fermentation and to increase the CGTase production from Bacillus sp. TS1-1 in fed batch fermentation. Optimisation of the C/N ratio in the feed stream was conducted in a 5 l fermenter, where feeding was initiated at constant rate of 0.02 hâˆ’1. In our initial screening process, the addition of nitrogen source boosted the growth of the microbes, but on the other hand reduced the CGTase production. The amount of tapioca starch and yeast extract was optimised in order to obtain a sufficient growth and thus, increased the CGTase production. Results were analysed using three-dimensional response surface plot, and the optimised values of carbon and nitrogen concentration of 3.30% (w/v) and 0.13% (w/v) were obtained, respectively. CGTase activity increased up to 80.12 U/ml, which is 13.94% higher as compared to batch fermentation (70.32 U/ml). This also led to 14.54% increment of CGTase production in fed batch culture as compared to the production before the optimisation. The CGTase activity obtained was close to the predicted value, which is 78.05 U/ml. Â© 2006 Elsevier B.V. All rights reserved. Keywords: Cyclodextrin glucanotransferase; C/N ratio; Fed batch; Central composite design